Examen especial a la cuenta de ingresos y gastos del gobierno autónomo descentralizado parroquial de “El Ideal”, del cantón Gualaquiza, provincia Morona Santiago, en el período 2014 - Ortega Ortega, Carmen Yolanda (2016)
This work called "Special Examination of Income and Expenses of Self-Government Decentralized Parish of" The Ideal ", the Canton Gualaquiza, Morona Santiago Province, in the period 2014", was carried out to fulfill the objective of making a special examination to the account of income and expenditure, with this approach, scientific, deductive and inductive methods are used to determine the reliability of information on income and expenses generated in the entity, in this context, direct observation was used and the interview applied the secretary-treasurer. To effectuate compliance with the above objective, proposed in the first phase, the preliminary knowledge that contemplate the context of the entity, according to planning the second phase, where the program execution of the examination was detailed questionnaires control intern who provided the data that facilitated establish the findings are presented as argued in the narrative bonds and their respective review in the analytical bonds, concluding with the presentation of the Final Report of the Review of Accounts Income and Expenses raised the applicable recommendations broken down according to schedule follow-up. Consequently, by applying the Special Review in the GAD Parish The Ideal, it is concluded that the laws and regulations established in this institution, are not timely met, so it is recommended to verify that compliance be given to them during the development of operations performed in orientation to the greater effectiveness of the expected return.